Control of local stress in semiconductor silicon structures - S. F. Sianko; V. A. Zelenin (Приборы и методы измерений)
Residual stress distribution in multilayer semiconductor structure is complicated and has a significant impact on device characteristics and yield, therefore their study is one of the actual tasks of modern device engineering. Purpose of the present work was to develop methods of estimation of actual residual stress distribution at the whole area of semiconductor structure and its elements as well.The estimation of residual stress distribution at the area of semiconductor structure was carried out on the basis of determining of local deformation of some areas of the structure by Makyoh topography. This method is based on consequent measurements of intensity of Makyoh image elements of the structure along the chosen direction followed by calculation of micro-geometrical profile and curvature radius.The estimation of residual stress of topological elements Si–SiO system was carried out by means of calculation of interference pictures obtained in a film-substrate gap after separating of film edge from substrate along open window perimeter.Analytical expressions relating semiconductor structure image characteristics with their deformation were developed by means of finite elements method. The expressions allow determining of local residual stress of chosen area of the structure. The examples of stress calculations in real structures are given.Proposed residual stress calculation methods allow to take into consideration character and curvature form of substrate, and also to estimate their magnitude in real topological elements of semiconductor circuits.